2021
DOI: 10.26417/623qdp44g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Middle Term Points in Total Score in the Context of Face to Face and Online Teaching

Abstract: The study aimed to investigate the differences between face-to-face and online teaching, as well as the effect of middle term points in total score in the context of face-to-face and online teaching. Correlational research design and a database of students’ attendance and results to get secondary data were used in the study. A random cluster sample of students from the bachelor's degree program was taken. The study demonstrated that there is a mean difference in the population or, equivalently, that the two-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The link between different domains of art, such as music, drawing or painting and sculpting is also part of current research work. Adams (2016) indicated the link of creativity between dance and drawing; at the same time, Xhomara (2017) revealed that 28.1% of the variance in art academic progress has been influenced by lecture attendance; and project-work impact significantly the students' academic results (Xhomara & Hala, 2021). Inside the art field is measured a high positive relationship among three components: artistic analysis of the idea, artistic practicing, and artistic skills (Perez-Fabello & Campos, 2011;Van Assche, 2017); meantime, approximately half of the variance in art achievement may be explained or accounted for by structured learning and practicing (Xhomara & Karabina, 2021).…”
Section: Relationship Between Didactic-artistic Tools and Artistic Sk...mentioning
confidence: 99%
“…The link between different domains of art, such as music, drawing or painting and sculpting is also part of current research work. Adams (2016) indicated the link of creativity between dance and drawing; at the same time, Xhomara (2017) revealed that 28.1% of the variance in art academic progress has been influenced by lecture attendance; and project-work impact significantly the students' academic results (Xhomara & Hala, 2021). Inside the art field is measured a high positive relationship among three components: artistic analysis of the idea, artistic practicing, and artistic skills (Perez-Fabello & Campos, 2011;Van Assche, 2017); meantime, approximately half of the variance in art achievement may be explained or accounted for by structured learning and practicing (Xhomara & Karabina, 2021).…”
Section: Relationship Between Didactic-artistic Tools and Artistic Sk...mentioning
confidence: 99%